A facile method to prepare flexible boron nitride/poly(vinyl alcohol) composites with enhanced thermal conductivity. (8th September 2017) - Zhang, Jun; Wang, Xiaona; Yu, Cuiping; Li, Qiulong; Li, Zhuo; Li, Chaowei; Lu, Huifen; Zhang, Qichong; Zhao, Jingxin; Hu, Ming; Yao, Yagang
Abstract: Polymer infiltrating filler-network has been actively researched recently to obtain composite materials with enhanced thermal conductivities. However, the long infiltration time blocks its wide application. In this study, we prepared hexagonal boron nitride (h-BN)/poly(vinyl alcohol) (PVA) composite by combining polymer infiltration with filler diffusion through the polymer to reduce infiltration time and form heat conduction paths. Base on this process, the maximum thermal conductivities of the obtained h-BN/PVA composites were 1.63 W/m·K and 8.44 W/m·K along the through-plane and in-plane directions, respectively. In addition, the composites displayed excellent heat dissipation performance when attached on top of a light emitting diode (LED) light strip. The research results indicate our approach is facile and capable of fabricating high performance thermal interface materials.